The Routledge research companion to popular music and gender - Hawkins, Stan (Routledge, Taylor & Francis Group, 2017)
Why is gender inseparable from pop songs? What can gender representations in musical performances mean? Why are there strong links between gender, sexuality and popular music? The sound of the voice, the mix, the arrangement, the lyrics and images, all link our impressions of gender to music. Numerous scholars writing about gender in popular music to date are concerned with the music industry's impact on fans, and how tastes and preferences become associated with gender. This is the first collection of its kind to develop and present new theories and methods in the analysis of popular music and gender. The contributors are drawn from a range of disciplines including musicology, sociology, anthropology, gender studies, philosophy, and media studies, providing new reference points for studies in this interdisciplinary field. Stan Hawkins's introduction sets out to situate a variety of debates that prompts ways of thinking and working, where the focus falls primarily on gender roles. Amongst the innovative approaches taken up in this collection are: queer performativity, gender theory, gay and lesbian agency, the female pop celebrity, masculinities, transculturalism, queering, transgenderism and androgyny. This Research Companion is required reading for scholars and teachers of popular music, whatever their disciplinary background. Stan Hawkins is Professor of Musicology at the University of Oslo, Norway, and Adjunct Professor at the University of Agder, Norway. His research fields involve music analysis, popular musicology, gender and culture. From 2010-2014 he has led a Norwegian state-funded project, Popular Music and Gender in a Transcultural Context. He is author of Settling the Pop Score (2002), The British Pop Dandy (2009), and Prince: The Making of a Pop Music Phenomenon (2011). His edited volumes include Music, Space & Place (2004), Essays on Sound & Vision (2007), Pop Music & Easy Listening (2011), and Critical Musicological Reflections (2012). He is currently one of the General Editors for the Ashgate Popular and Folk Music Series.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Popular music; Sex role in music; Gender identity in music; Geschlechterrolle; Unterhaltungsmusik; Geschlechterforschung